Adobe creative suite 2 - Golding, Mordy; Safari eBooks (Indianapolis, Ind. : Sams, 2006)
Adobe's Creative Suite brings together the Photoshop, Illustrator, Acrobat, InDesign and GoLive software and a new file management tool called Version Cue.
Using Adobe Photoshop CS -- Using Adobe ImageReady CS -- Using Adobe Illustrator CS -- Using Adobe InDesign CS -- Using Adobe GoLive CS -- Using Adobe Acrobat 6.0 Professional -- Using Adobe Version Cue.
Includes index.
Available also in a print edition.
Electronic reproduction.
Mode of access: World Wide Web.
Made available through: Safari Books Online, LLC.
Keywords: Adobe Acrobat; Adobe GoLive; Adobe Illustrator (Computer file); Adobe InDesign; Adobe Photoshop; Adobe Version Cue (Computer file); ImageReady; Computer graphics; Desktop publishing; Web sites -- Design; Electronic books